Anisocoria caused by an abscess in the cisterna interpeduncularis in a patient with bacterial meningitis. Issue 3 (19th February 2019) - Watanabe, Toshiyuki Tony; Itaya, Sakiko; Kamata, Tomoyuki
Abstract: When bacterial meningitis is suspected in an emergency situation, a lumbar puncture is usually performed to obtain a cerebrospinal fluid culture for identifying the causative microorganism. However, in cases in which signs and symptoms of high intracranial pressure are obvious, lumbar puncture is contraindicated unless brain herniation is ruled out. We encountered a case of bacterial meningitis with anisocoria, which we regarded as a sign of high intracranial pressure, and refrained from performing a lumbar puncture. Subsequently, high intracranial pressure and brain herniation were ruled out, and abscess formation in the cisterna interpeduncularis was observed to have caused anisocoria. Thus, when anisocoria is observed in patients with bacterial meningitis, the cause should be established by methods such as magnetic resonance imaging, and only if the cause of anisocoria is obvious and the possibility of high intracranial pressure is low, should diagnostic lumbar puncture be performed.